Reactor bioquímico para producción de etanol por fermentación de biomasa de desecho (2020)
This document presents the development of a biochemical reactor in which the fermentation process is carried out in order to obtain ethanol, after distillation of the ferment produced. The reactor is of type Batch discontinuous and gathers the set of peculiarities that favor the growth of yeasts, such as constant agitation, controlled temperature, oxygen injection and CO2 extraction generated from the chemical reaction, which are monitored to establish an enabling environment in which yeasts carry an adequate growth process and produce a good amount of ethanol. After the construction of the reactor with the desired characteristics, the testing phase is carried out to determine the optimal fermentation conditions, such as the initial concentration that is implanted in the reactor, to finally establish the results and conclusions of the work carried out, including the distillation process that is carried out to obtain ethanol separated from the other liquids present in the ferment.